Pemertahanan Bahasa Leukon di Kabupaten Simeulue - Yusri Yusri; Hasanul Amri (Jurnal Dedikasi Pendidikan, 2018)
This research is titled "Leukon Language Defense in Simeulue District." The formulation of the problem in this research is (1) how is the Leukon language defense level in the Leukon community of Alafan District of Simeulue Regency? The level of defense is focused on several domains, namely family, education, neighborhood, religion, and customs; (2) how does Leukon language speech effort keep Leukon language? This research uses two approaches, namely qualitative and quantitative. The research is descriptive. The population in this study was Leukon speech community in two villages, Langi and Lafakha. The sample of research is 60 people divided into three groups, namely adolescents, adults, and parents of each group amounted to 20 people. The data were collected using interview technique and spreading questionnaires or questionnaires. The results of this study indicate that the level of Leukon language defense in five domains tend to be positive, that is 60%. The lowest defense occurs in the educational domain of the percentage, which is 5%. In the meantime, the efforts of the Leukon community to maintain their local languages are classified as "Nanga-Nanga," and "Inafi," Overall of all groups (adolescents, adults and parents) the percentage of Leukon language defense is 61.50% 35 samples. That is, Leukon language level of defense is high.